Improving Learning Outcomes of Mathematics Content Theme 8 on Second Grade Students of SDN 1 Karangpucung for the 2019/2020 Academic Year Using the Zoom Cloud Meeting Application - Salecha Gunansyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this research is to improve student learning achievement in online distance learning. The variable that is the target of the change is the learning outcomes of students in the mathematics content of the Time Measurement material in Standard Units, while the action variable used is the use of the Zoom Cloud Meeting application. The form of this research is Classroom Action Research (CAR) using a cycle model consisting of two cycles. Each cycle consists of 4 stages, namely: planning, implementing actions, observing, and reflecting. The subjects of the research were the 2th students of SD Negeri 1 Karangpucung, totaling 32 children. Data collection techniques using tests, observations, and documentation. The data analysis technique uses a qualitative analysis model, which includes 3 components, namely data reduction, data presentation, and verification. Based on the results of the study, it can be concluded that there is an increase in learning outcomes for the Mathematics content of the Time Measurement material in Standard Units after classroom actions are carried out by applying the Zoom Cloud Meeting application. Before the action the percentage of students who reached the passing grade was 37%. In the first cycle the percentage of students who reached the passing grade was 57%. In the second cycle the percentage of students who reached the passing grade was 93%.